2018
DOI: 10.1097/md.0000000000012061
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Internet-delivered cognitive-behavioral therapy for the management of chronic pain in children and adolescents

Abstract: Background:Pediatric chronic pain is relatively common in the world. Although cognitive behavior therapy (CBT) has been shown to be efficacious in children and adolescents, it is generally recognized that availability and accessibility of CBT are limited. While Internet-delivered cognitive-behavioral therapy (ICBT) performs better in these areas.Objectives:This systematic review aims to evaluate the clinical effects of ICBT for chronic pain in youth when compared with the control treatments.Methods:We searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 41 publications
0
32
0
1
Order By: Relevance
“…To the best of our knowledge, there are no systematic reviews that specifically investigate digital interventions for the management of chronic health conditions in children (aged <13 years). Furthermore, reviews investigating digital interventions for young people with chronic health conditions typically do not include children aged below 10 years [ 35 ], or, if they do, only a minority of the interventions included in the reviews include children aged below 13 years [ 15 , 36 - 38 ], recognizing that there are “fewer interventions targeting…the extreme pediatric age ranges of early childhood and emerging adulthood” [ 16 ]. The reviews spanning childhood and adolescence note important differences between these age groups.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are no systematic reviews that specifically investigate digital interventions for the management of chronic health conditions in children (aged <13 years). Furthermore, reviews investigating digital interventions for young people with chronic health conditions typically do not include children aged below 10 years [ 35 ], or, if they do, only a minority of the interventions included in the reviews include children aged below 13 years [ 15 , 36 - 38 ], recognizing that there are “fewer interventions targeting…the extreme pediatric age ranges of early childhood and emerging adulthood” [ 16 ]. The reviews spanning childhood and adolescence note important differences between these age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews and meta-analyses have shown promising outcomes for e-therapies in a range of populations (e.g. Barak et al, 2008 ; Tang et al, 2018 ). The NHS Long Term Plan, published before the COVID-19 outbreak, detailed hopes for increasing the availability of digital health care ( NHS, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Web-based intervention is expected to be an effective way to cope with chronic neck pain and related issues 13,14) . Web-based interventions have the following benefits compared to conventional methods.…”
Section: Ofmentioning
confidence: 99%